2012
DOI: 10.1021/la204156d
|View full text |Cite
|
Sign up to set email alerts
|

Atom Probe Tomography Characterization of Thin Copper Layers on Aluminum Deposited by Galvanic Displacement

Abstract: Abstract″Ultrathin″ metallization layers on the order of nanometers in thickness are increasingly used in semiconductor interconnects and other nanostructures. Aqueous deposition methods are attractive methods to produce such layers due to their low cost, but formation of ultrathin layers has proven challenging, particularly on oxide-coated substrates. This work focused on the formation of thin copper layers on aluminum, by galvanic displacement from alkaline aqueous solutions. Analysis by atom probe tomograph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
17
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 33 publications
3
17
0
Order By: Relevance
“…The presence of hydride at the Al/Al(OH) 3 interface is consistent with findings that the pH-dependence of the dissolution potential tracks closely with that of the Nernst potential of hydride oxidation [48,49]. APT images of the interfacial region indicated that hydride is dispersed at the nanoscale, as opposed to being segregated in isolated domains, thus implying that the same electrochemical potential applies at both Al and AlH 3 sites [47]. Expressing this potential in terms of both the Al and AlH 3 oxidation reactions yields the constraint, m Al À m 0…”
Section: Stress Generation Mechanismssupporting
confidence: 85%
See 1 more Smart Citation
“…The presence of hydride at the Al/Al(OH) 3 interface is consistent with findings that the pH-dependence of the dissolution potential tracks closely with that of the Nernst potential of hydride oxidation [48,49]. APT images of the interfacial region indicated that hydride is dispersed at the nanoscale, as opposed to being segregated in isolated domains, thus implying that the same electrochemical potential applies at both Al and AlH 3 sites [47]. Expressing this potential in terms of both the Al and AlH 3 oxidation reactions yields the constraint, m Al À m 0…”
Section: Stress Generation Mechanismssupporting
confidence: 85%
“…The primary anodic reaction during corrosion is the oxidation of Al atoms to form Al þ3 ions incorporated into the Al(OH) 3 surface film; at the same time, aluminate ions dissolve from this film into the saturated alkaline solution [45]. Also, analytical evidence from Secondary Ion Mass Spectroscopy and Atom Probe Tomography (APT) indicate continuing formation of aluminum hydride (AlH 3 ) during alkaline dissolution [46,47]. The presence of hydride at the Al/Al(OH) 3 interface is consistent with findings that the pH-dependence of the dissolution potential tracks closely with that of the Nernst potential of hydride oxidation [48,49].…”
Section: Stress Generation Mechanismsmentioning
confidence: 99%
“…Such a transition for a MgO and Si cluster was also shown in previous papers. 7,8 We studied the field evaporation process of ZnO in APT. The evaporated ion species are Zn 2þ , ZnO 2þ , O 2 þ , and O þ , in good agreement with experiments.…”
Section: Discussionmentioning
confidence: 99%
“…APT was originally developed for the analysis of steels and alloys but in recent years it has also been adapted for the characterization of semiconductors and insulators with the assistance of ultrafast laser pulses. Metal oxides with thicknesses of the order of 10 nm, such as NiO, 3,4 Fe 1Àx O, 5 Al 2 O 3 , 6,7 MgO, [8][9][10][11] and ZnO 9-12 deposited on metal tips, have been analyzed successfully. A variety of positively charged atoms and molecules are observed in the mass spectra.…”
Section: Introductionmentioning
confidence: 99%
“…Whereas the portion of the surface film on Al contacting the alkaline solution is composed of aluminum oxide or hydroxide, 21 evidence from our laboratory supports previous findings by Perrault that the interior of the film contains appreciable (AlH 3 ). 22 We detected interfacial aluminum hydride within the surface film by secondary ion mass spectrometry and atom probe tomography (APT) 23,24 and showed that the electrochemical potential at the metalÀfilm interface is close to the Nernst potential of the hydride oxidation reaction. 25,26 Because borohydride ions in solution can mediate ELD of copper from alkaline baths, a similar role for surface AlH 3 seems possible 27,28 We show here that simple galvanic displacement from alkaline baths can deposit thin Cu metal layers on Al in certain ranges of pH, copper concentration, and process time.…”
Section: à16mentioning
confidence: 99%